2020
DOI: 10.3390/horticulturae6040084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High CO2 Treatment and MA Packaging on Sensory Quality and Physiological-Biochemical Characteristics of Green Asparagus (Asparagus officinalis L.) during Postharvest Storage

Abstract: Green asparagus is vulnerable to thrips that carry microorganisms and cause deterioration in quality. The effects of 60% CO2 treatment, which is used to kill thrips, combined with perforated (P) or modified atmosphere (MA) packages during cold storage, on the sensory quality and physiological–biochemical characteristics of asparagus were investigated. MA packaging yielded an asparagus shelf-life five days longer than P packaging. The 60% CO2 treatment for 48 h at 4 °C packaged with MA film (CO2-48 h-4 °C-MA) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…As a way of regulating the CO 2 content in the film, the oxygen transmission film (OTR) allows the transmission of O 2 within the fruit’s environment [ 11 ] and the fruit’s respiration is responsible for changes in the gas content. Following discussion from previous studies, peppers have a tolerance level of 5% CO 2 in MAP conditions [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a way of regulating the CO 2 content in the film, the oxygen transmission film (OTR) allows the transmission of O 2 within the fruit’s environment [ 11 ] and the fruit’s respiration is responsible for changes in the gas content. Following discussion from previous studies, peppers have a tolerance level of 5% CO 2 in MAP conditions [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electrolyte leakage (EL) was determined following the Wang [ 11 ] method. Sweet pepper mesocarp samples (0.5 g) were immersed in 0.4 M mannitol (25 mL) and shaken for 3 h at room temperature, after which the EL was measured immediately with a handheld meter (HI 9813-6 Portable pH/EC/TDS/°C Meter; Hanna Instruments, Padova, Italy).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the quality of A. officinalis circulating in the market is uneven, which seriously affects economic benefits and its expansion and application. Most of previous studies have focused on improving transport efficiency, storage process, [21] processing procedure, [22] preharvest factors [23] and other external conditions to improve the quality of A. officinalis . For example, Wang et al [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Most of previous studies have focused on improving transport efficiency, storage process, [21] processing procedure, [22] preharvest factors [23] and other external conditions to improve the quality of A. officinalis . For example, Wang et al [21] . studied the effects of 60 % CO 2 concentration treatment combined with perforated package (P) and modified atmosphere package (MA) on the sensory quality, physiological and biochemical characteristics of post‐harvest A. officinalis ; the results showed that the experimental condition in which MA membrane was treated with 60 %‐CO 2 at 4 °C for 48 h (CO2‐48 h‐4 °C‐MA) could strongly inhibit the growth of the microflora of during A. officinalis storage and effectively maintain the contents of soluble solids and electrolytes.…”
Section: Introductionmentioning
confidence: 99%